LITERASI DEMOKRASI: Sosialisasi di Desa Karama Kec. Tinambung: Sosialisasi di Desa Karama Kec. Tinambung - Farhanuddin; Zainuddin Losi; Muhammad Sulthan (Lembaga Penelitian Pengabdian kepada Masyarakat, 2025)
Abstract Democratic literacy is a fundamental aspect of fostering political participation in society, particularly in rural areas. This article presents a community service program aimed at enhancing democratic understanding in Karama Village, Tinambung District, West Sulawesi. The implementation methods included three main approaches: (1) interactive lectures on basic democratic concepts, (2) participatory discussions on village-level democratic practices, and (3) motivational sessions to encourage active citizen engagement. The results demonstrated significant improvement in community awareness, especially among youth, regarding their rights and responsibilities as citizens. This participation was evident not only in elections but also in involvement in village development programs. Key challenges identified included limited access to information, lack of formal political education, and insufficient dialogue platforms. The proposed solution involves strengthening multi-stakeholder collaboration between village government, academics, civil society organizations, and local media. This initiative proves that participatory educational approaches effectively cultivate democratic awareness. The main recommendation is the need for sustainable programs with modules better adapted to rural community characteristics. Keywords: democratic literacy, political participation, community service, political education, rural community